Lie symmetries and reductions via invariant solutions of general short pulse equation - Mobeen Munir, Muhammad; Bashir, Hajra; Athar, Muhammad (Frontiers in Physics, 2023)
Lie symmetry opens the way to get the similarity solutions as an exact solutions for the differential equations. Symmetry method by Lie provide the ease to attain the exact solutions of non-linear PDEs by the certain algorithm. In this paper, we determined the Lie symmetries for one of the general case of SPE with its optimal system and reductions. The invariant solutions are evaluated for the symmetries of generalized SPE. Graphical behavior of the transformed points of the functions are obtained by using maple.